Implantação do modelo dinâmico inercial rígido em sistemas hidráulicos no software EPANET - BOTTA, Gustavo Marino (2014)
As a research problem, we sought to develop the ability to simulate hydraulic events in the distribution network taking into account the effect of inertia. The EPANET software has advantages such as: be in the public domain, to be used in several scientific essays, be one of the models most used in different countries, the most reliable and have compatibility with several other simulators. Still has the disadvantage to do not use in their calculations the effects of inertia. As the objective of this work, we had the implementation of the EPANET software, the simulation of the Dynamic Model Inertial Drive software (DMID) for analysis of slow transient flows in non-steady state facilities to penstocks and subsequently comparing the model DMID with the Gradient Method model (method of calculation used by EPANET). As a methodology, source files were acquired from EPANET software, conducted the analysis of software engineering, developed the algorithms for DMID model and made experimental research comparing the Model DMID with Gradient Method. This simulation is important, as monitoring the load and the flow on hydraulic installation is required to detect the supply levels and pressure surges that can cause disruptions in the pipeline. With the introduction of DMID, in the EPANET software, this fault has been resolved, because the DMID improved EPANET calculation engine using algorithms that consider the effects of inertia. Thus, now it can be detected pressure peaks and prevent disruptions of pipes or fittings. The expansion of the Software EPANET was possible where the DMID simulates the dynamic model taking into account the inertia. The simulation in daily life has been improved seen that besides the contribution to quick solutions with now costs can also provide pressure peaks and possible disruptions of pipes. Thus, it is concluded that for the study of the hydraulic system, the Dynamic Model Inertial Drive software (DMID) is presented as a very interesting solution.